Orobanche salviae (Orobanchaceae), new to the flora of the Iberian Peninsula - Mercadé López, Arnau; Pérez-Haase , Aaron (Mediterranean Botany, 2024)
Orobanche salviae is a European orophyte and considered an exclusive parasite of Salvia glutinosa. Here we provide the first report of the species for the Iberian Peninsula, which we discovered recently in the eastern Catalan Pyrenees. The closest reliable known localities are in the French Maritime Alps, although it was also previously reported with uncertainty from the French Pyrenees. The new found populations are located at the absolute western limit of the distribution of the species. We provide a description of its distribution, habitat and, given its rarity, we suggest a category of threat following the IUCN criteria.